Analisis Pengaruh Subsidi BBM dan Belanja Infrastruktur Fisik terhadap Pertumbuhan Ekonomi dan Tingkat Kemiskinan di Indonesia (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Poverty remains a complex and multidimensional global issue. Indonesia, as a developing country, applies pro-poor theories to alleviate poverty through economic growth and expansionary fiscal policies that can create a multiplier effect. Expansionary fiscal policies, such as fuel subsidies and physical infrastructure spending, are expected to reduce poverty and boost economic growth in order to achieve the 2030 SDGs and Indonesia Emas 2045. The purpose of this study is to analyse the effect of fuel subsidies and physical infrastructure spending on poverty levels, mediated by economic growth in Indonesia from 1995 to 2024. The data used is secondary data and a 30-year time series, which is quantitative research through path analysis using the STATA application. The results show that economic growth affects poverty levels but plays a weak role as a mediating variable between fiscal spending and poverty levels in Indonesia. Fuel subsidies do not affect poverty, while physical infrastructure spending has been shown to have a significant effect through job creation. This is in line with Keynesian theory and public expenditure, which emphasises government spending on productive and targeted sectors to create a multiplier effect that can drive growth and reduce poverty levels.